2010
DOI: 10.1002/btpr.472
|View full text |Cite
|
Sign up to set email alerts
|

Serum starvation improves transient transfection efficiency in differentiating embryonic stem cells

Abstract: Control of genetic expression is a critical issue in the field of stem cell biology, where determining a cell fate or reprogramming adult somatic cells into pluripotent cells has become a common experimental practice. In turn, for these cells to have therapeutic clinical potential, techniques for controlling gene expression are needed that minimizes or eliminates the risk of oncogenesis and mutagenesis. Possible routes for achieving this outcome could come in the form of a transient nonviral gene delivery syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Many studies have revealed that the effi ciency of transient transfection could be increased by using serum-free medium such as Opti-MEM to increase foreign DNA uptake. This effect has been shown particularly in application of cationic nanoparticles that are taken up by cells via endocytosis (12). In this study, although both transfection mixtures were prepared using Opti-MEM, the transfection effi ciency was signifi cantly low in H9 T-cells.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Many studies have revealed that the effi ciency of transient transfection could be increased by using serum-free medium such as Opti-MEM to increase foreign DNA uptake. This effect has been shown particularly in application of cationic nanoparticles that are taken up by cells via endocytosis (12). In this study, although both transfection mixtures were prepared using Opti-MEM, the transfection effi ciency was signifi cantly low in H9 T-cells.…”
Section: Discussionmentioning
confidence: 76%
“…Although there are many reports about the cellular toxicity of Lipofectamine 2000 in comparison with other transection reagents such as Turbofect, there are just few published studies on toxicity of Lipofectamine 3000 (9,19,(20)(21)(22)(23). In one study, Lipofectamine CRISPRMAX was compared with Lipofectamine 3000 and Lipofectamine RNAiMAX, and signifi cant effi ciency with less toxicity of Lipofectamine CRISPRMAX was shown (12,(23)(24)(25)(26). In this study, Lipofectamine 3000 showed signifi cant cellular toxicity on H9T-cells after transfection with pCDH vector.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of the viability of HeLa cells upon exposure to capsules was measured using different incubation procedures: (i) first 4 h of incubation in cell growth medium without fetal bovine serum (FBS), and then 20 h of incubation in the medium supplemented with FBS; (ii) 24 h of incubation in the cell growth medium supplemented with FBS. The two conditions were used as the transfection of cells varies upon the presence/absence of FBS [ 53 , 54 ]. The capsule concentration was quantified in terms of delivered encapsulated DEX-blue m DEX-blue [pg/cell].…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the MEFs (20,000 cells/well) were seeded in 96-well plates and incubated at 37 ∘ C (5% CO 2 ). The culture medium was subsequently replaced with serum-free medium for serum starvation after cell adherence to obtain a better gene transfer efficiency [25]. After 12h of serumfree incubation, pmPPY-pSox9 nanoparticles (9:1, 15:1, 30:1, 50:1, 100:1, 150:1, 200:1, and 300:1) were transferred, and the Lipofectamine 2000-Sox9 and PEI-Sox9 groups (multiple dilutions of PEI with PBS: 100-fold, 200-fold, 250-fold, 350fold, 500-fold, 1000-fold, and 2000-fold) were used as positive controls according to the manufacturer's protocol under the same conditions.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%